THE NEED FOR REPRODUCTIVE HEALTH EDUCATION ABOUT MENARCHE IN PRIMARY SCHOOL STUDENTS IN MOJOKERTO CITY - Catur Prasastia lukita Dewi; Lutfi Wahyuni (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2024)
The onset of menstruation will be a traumatic event for some children who do not prepare themselves in advance. School-aged children need information about the menstrual process and health during menstruation. Children will have difficulty facing their first menstruation if they have never known about it before. This shows that school age children need reproductive health education in facing menarche. However, in reality, many school-aged children still have relatively low knowledge of reproductive health. The aim of this research is to identify the need for reproductive education regarding menarche among elementary school students in Mojokerto City. This research method uses a descriptive analytical research design with a case sectional approach. Samples were taken based on purposive sampling. Data collection was carried out through interviews using a reproductive education needs questionnaire. From the research results, it was found that the high level of need for reproductive health education, especially information on menarche, was due to the absence of a curriculum in elementary schools that discussed this issue.